Light‐Induced Electric Field Enhanced Self‐Powered Photodetector Based on Van der Waals Heterojunctions. Issue 1 (28th November 2022) - Shang, Huiming; Gao, Feng; Dai, Mingjin; Hu, YunXia; Wang, Shuai; Xu, Bo; Wang, Peng; Gao, Bo; Zhang, Jia; Hu, PingAn
Abstract: Self‐powered photodetectors have attracted widespread attention due to their low power consumption which can be driven by the built‐in electric field instead of external power, but it is very difficult to achieve high responsivity and fast response speed concurrently. Here, a self‐powered photodetector with light‐induced electric field enhancement based on a 2D InSe/WSe2 /SnS2 van der Waals heterojunction is designed. The light‐induced electric field derived from the photo‐generated electrons of SnS2 accumulated at the SnS2 /WSe2 interface produces an additional negative gate voltage applied to the WSe2 layer, which enhances the built‐in electric field in the InSe/WSe2 /SnS2 heterojunction. Accordingly, the photocurrent and photoresponse speed of the heterostructure device are largely improved. The self‐powered photodetector based on the InSe/WSe2 /SnS2 heterostructure exhibits a high responsivity of 550 mA W −1, which is a 50 times increase compared to the InSe/WSe2 photodetector, and the response speed (110/120 µs) is one order of magnitude faster than that of the InSe/WSe2 photodetector. The high responsivity and fast speed are caused by the stronger built‐in electric field modulated by a light‐induced electric field, which can separate carriers effectively and reduce drift times. This device architecture can provide a new avenue to fabricate high‐responsivity, fast self‐power photodetectors by utilizing the van der Waals heterojunction. Abstract : The new architecture of self‐powered photodetectors allows for simultaneously enhancing the generation of photocurrent and photo‐response speed in van der Waals heterojunction photodetectors of InSe/WSe2 in InSe/WSe2 /SnS2 through a light‐induced electric field.